Education.com
Try
Brainzy
Try
Plus

Thermochemistry Study Guide (page 2)

based on 2 ratings
By
Updated on Sep 24, 2011

Example:

Calculate the standard enthalpy of reaction for the combustion of methane:

CH4(g) + O2(g) → H2O(g) + CO2(g)

Solution:

Balance the chemical equation:

CH4(g) + 2O2(g) → 2H2O(g) + CO2(g)

Set up the mathematical equation:

= ( products) – ( reactants)

so, = (2 [H2O(g)] + [CO2(g)]) – ( [CH4(g)] + 2 [O2(g)])

= (2(–242) + (–393.5)) – ((–75) + 2(0))

[Note: O2 is oxygen's standard state.)

= –877.5 – (–75) = –802.5 = –803 kJ

As expected, the combustion (burning) of methane is exothermic.

Hess's Law

Many reactions are difficult to calculate with the standard enthalpies of formation or calorimetry. Enthalpy is a state function that means that the calculation is independent of the pathway or calculation. Hess's Law states that an enthalpy of a reaction can be calculated from the sum of two or more reactions.

Example 1:

Calculate the enthalpy for ice, H2O(s), yielding steam, H2O(g), given the following equations:

ΔH (kJ)
H2O(s) → H2O(I)   6.02
H2O(I) → H2O(g)   44.0

Knowing we need to sum the previous equations to produce H2O(s) → H2O(g), we get

H2O(s) → H2O(I)   6.02
H2O(I) → H2O(g)   44.0
H2O(s) → H2O(g)   50.0

The yield arrow (→) acts like an equals sign. Therefore, identical substances on both the right and left sides, regardless of which equations, can be canceled. The sum of the reaction and sum of the enthalpies are added to create the wanted equation and final answer.

Example 2:

Calculate the enthalpy change for C(s) + 2H2(g) → CH4(g) given the following equations:

ΔH (kJ)
C(s) + O2(g) →CO2(g)   –393.5
  –285.8
CH4O2(g) →CO2(g) + 2H2O(l)   –890.3

Solution 2:

This problem requires more effort. The two rules of Hess's Law must be applied:

  • Equations can be reversed if the sign on ΔH is changed.
  • Equations can be multiplied by any number to be able to cancel out substances in other equations. The ΔH must also be multiplied by the same value.

We want C(s) + 2H2(g) → CH4(g). So,

C(s) + O2(g) → CO2(g) – 393.5

CO2(g) + 2H2O(l) → CH4(g) + 2O2(g) + 890.3

(equation is reversed to get CH4 on the right)

C(s) + 2H2(g) → CH4(g) – 74.8 kJ

(–393.5 + 890.3 + 2(–285.8)= –74.8)

View Full Article
Add your own comment